America the beautiful a tribute to God & country ([S.l.] Reader's Digest Chicago, IL Distributed by Questar, 2002)
Presents video tours of various national parks, landmarks and other scenic wonders. Also presents musical tributes as America's most breathtaking scenery is accompanied by songs and inspirational hymns and melodies
[v. 1.] America the beautiful, a tribute ro god & country
DVD, Dolby digital
1
Keywords: Popular music -- United States; United States -- Description and travel